Molecular phylogenetics of Euploca (Boraginaceae): homoplasy in many characters, including the C4 photosynthetic pathway. (18th January 2022) - Frohlich, Michael W; Sage, Rowan F; Craven, Lyn A; Schuster, Sebastian; Gigot, Guillaume; Hilger, Hartmut H; Akhani, Hossein; Mahdavi, Parastoo; Luebert, Federico; Weigend, Maximilian; Thulin, Mats; Doyle, Jeff J; et al.
Abstract: We present a phylogenetic analysis using plastid ( matK, rbcL ) and nuclear (nrITS) DNA for diverse Euploca spp. (formerly Heliotropium section Orthostachys) from the worldwide distribution of a genus and including species encompassing the wide physiological and morphological diversity of the genus. Our results indicate that some remarkably complex features arose multiple times in parallel in Euploca, including attributes of its subsections under section Orthostachys, notably plants that, above ground, consist almost entirely of inflorescences. To elucidate in greater detail the distribution of C4 species in Euploca and Heliotropium s.s ., we made > 800 δ  13 C determinations, including some from the traditional genus Tournefortia . We greatly increase the number of proven C4 species in Euploca, but found none outside Euploca. Of the tested Euploca spp., c. 28% are C3 or intermediate in carbon fixation pathway. Our phylogenetic results indicate four parallel/convergent acquisitions of C4 photosynthesis or fewer origins with subsequent loss in some species.